Long-Term Immunocastration Protocols Successfully Reduce Testicles’ Size in Bísaro Pigs - Gustavo Paixão; Sofia Botelho Fontela; Jorge Marques; Alexandra Esteves; Rui Charneca; Rita Payan-Carreira (Animals, 2021)
This study aimed to find a suitable immunocastration protocol for male Bísaro pigs (BP) due to the breed and production system particularities. Twenty-five male BP were treated with Improvac® according to three protocols: using two (GrpE2 and L2) or three vaccinations (GrpL3) and starting at 9 (GrpE2) or 13 weeks old (GrpL2 and L3). Eleven animals were kept as intact males (GrpC). Scrotal measurements and the morphometry of the testes and epididymides collected at slaughter were used to survey the effectiveness of the immunocastration compared with the age-matched intact controls. Animals in groups E2 and L3 were kept until 57 weeks, after a second vaccination cycle at 49 and 53 weeks of age. Scrotal dimensions decreased to almost initial values in treated animals until 17 (GrpE2) and 21 weeks (GrpL2 and L3), thereafter increasing to post-pubertal values until around 29 or 37 weeks of age for groups E2 and L2, respectively, but only at 41 weeks in group L3. Between 41 and 49 weeks, scrotal dimensions were similar in treated and control animals, decreasing to the predicted pre-puberty size after the second cycle of vaccination. This study suggests the most suited protocol for males slaughtered at older ages includes three administrations of Improvac® starting at 3 months of age, followed by a second vaccination cycle.